Trace element and OH content of quartz grains in the Amazon river: Potential application in provenance analysis - R. Stalder; D. Jaeger; S. Andò; E. Garzanti; C.M. Chiessi; A.O. Sawakuchi; T. Ludwig; M. Strasser (Sedimentary Geology, 2025)

Japan Trench event stratigraphy: First results from IODP giant piston coring in a deep-sea trench to advance subduction zone paleoseismology - Michael Strasser; Ken Ikehara; Charlotte Pizer; Takuya Itaki; Yasufumi Satoguchi; Arata Kioka; Cecilia McHugh; Jean-Noel Proust; Derek Sawyer; J. Everest; L. Maeda; K. Hochmuth; et al. (Marine Geology, 2024)

The effects of dietary amino acid balance on post-embryonic development in a lubber grasshopper - John Hatle; Connor R. Clark; Parker Agne; Nicholas Strasser; Juliana Arcaro; Emma N. Kordek; Kendal Rogers; Clancy A. Short; Zachary Sahni; Sean Sullivan; Brooke Reams; Selena Halleak (Journal of Insect Physiology, 2023)

The increasing threat to European forests from the invasive foliar pine pathogen, Lecanosticta acicola - K. Tubby; K. Adamčikova; K. Adamson; M. Akiba; I. Barnes; P. Boroń; H. Bragança; T. Bulgakov; N. Burgdorf; P. Capretti; T. Cech; M. Cleary; et al. (Forest Ecology and Management, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Ground speed and planter downforce influence on corn seed spacing and depth - S. A. Badua; A. Sharda; R. Strasser; I. Ciampitti (Precision Agriculture, 2021)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Epistemological dimensions of the water–energy–food nexus approach: reply to discussions of “Challenges in operationalizing the water–energy–food nexus” - C. Cudennec; J. Liu; J. Qi; H. Yang; C. Zheng; A. K. Gain; R. Lawford; L. de Strasser; P. T. Yillia (Hydrological Sciences Journal, 2018)

Challenges in operationalizing the water–energy–food nexus - J. Liu; H. Yang; C. Cudennec; A.K. Gain; H. Hoff; R. Lawford; J. Qi; L. de Strasser; P.T. Yillia; C. Zheng (Hydrological Sciences Journal, 2017)

Exogenous glycine betaine and proline play a protective role in heat-stressed barley leaves ( Hordeum vulgare L.): A chlorophyll a fluorescence study - A. Oukarroum; S. El Madidi; R. J. Strasser (Plant Biosystems, 2012)

The use of JIP test to evaluate drought-tolerance of transgenic rice overexpressing OsNAC10 - Mark C. F. R. Redillas; Reto J. Strasser; Jin Seo Jeong; Youn Shic Kim; Ju-Kon Kim (Plant Biotechnology Reports, 2011)

Increased P2X7R expression in atrial cardiomyocytes of caveolin-1 deficient mice - K. Barth; C. Pfleger; A. Linge; J. A. Sim; A. Surprenant; N. Steinbronn; R. H. Strasser; M. Kasper (Histochemistry and Cell Biology, 2010)

Localization of plant N‐glycan processing enzymes along the secretory pathway - R. Strasser (Plant Biosystems, 2009)

Foodborne outbreak of hepatitis A, November 2007–January 2008, Austria - D. Schmid; R. Fretz; G. Buchner; C. König; H. Perner; R. Sollak; A. Tratter; M. Hell; M. Maass; M. Strasser; F. Allerberger (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Response of plants to ectomycorrhizae in N-limited conditions: which factors determine its variation? - A. Corrêa; R. J. Strasser; M. A. Martins-Loução (Mycorrhiza, 2008)

Receptor-independent sensitization of the adenylyl cylase after chronic treatment with cyclosporine A - G. Simonis; T. Christ; S. K. Bährle; M. Pena; S. P. Schoen; R. Marquetant; U. Ravens; R. H. Strasser (Naunyn-Schmiedeberg's Archives of Pharmacology, 2008)

JIP test for fast fluorescence transients as a rapid and sensitive technique in assessing the effectiveness of arbuscular mycorrhizal fungi in Zea mays : Analysis of chlorophyll a fluorescence - M. K. Rai; S. Shende; R. J. Strasser (Plant Biosystems, 2008)

Association of OPRM1 A118G variant with the relative reinforcing value of nicotine - R. Ray; C. Jepson; F. Patterson; A. Strasser; M. Rukstalis; K. Perkins; K. G. Lynch; S. O’Malley; W. H. Berrettini; C. Lerman (Psychopharmacology, 2006)

Analysis of mechanisms contributing to AraC-mediated chemoresistance and re-establishment of drug sensitivity by the novel heterodinucleoside phosphate 5-FdUrd-araC - S. Maier; S. Strasser; P. Saiko; C. Leisser; S. Sasgary; M. Grusch; S. Madlener; Y. Bader; J. Hartmann; H. Schott; R. M. Mader; T. Szekeres; et al. (Apoptosis, 2006)

Are Mycorrhiza Always Beneficial? - A. Corrêa; R. J. Strasser; M. A. Martins-Loução (Plant and Soil, 2006)

Kinetics of delayed chlorophyll a fluorescence registered in milliseconds time range - V. Goltsev; P. Chernev; I. Zaharieva; P. Lambrev; R. J. Strasser (Photosynthesis Research, 2005)

Influence of histamine release on postoperative vomiting (POV) following gynaecological laparoscopic surgery - K. Kimura; D. Rsch; C. Strasser; M. Lengkong; H. Wulf; M. Koller; I. Celik (Inflammation Research, 2004)

The effects of hippocampal lesions in homing pigeons on a one-trial food association task - R. Strasser; V. P. Bingman (Journal of Comparative Physiology A, 1999)

Molecular cloning of cDNA encoding N-acetylglucosaminyltransferase II from Arabidopsis thaliana - R. Strasser; H. Steinkellner; M. Borén; F. Altmann; L. Mach; J. Glössl; J. Mucha (Glycoconjugate Journal, 1999)

The extracellular matrix in hibernating myocardium - a significant factor causing structural defects and cardiac dysfunction - A. Elässer; M. Schlepper; R. Zimmermann; K.-D. Müller; R. Strasser; W.-P. Klövekorn; J. Schaper (Molecular and Cellular Biochemistry, 1998)